Anorectal Melanoma: Unexpected tumor in unexpected population - Alkhamiss, Abdullah S.; Al Abdulmonem, Waleed I.; Alsalloom, Abdulaziz A.; Alsolai, Ahmed M.; Alorini, Mohammed A.; Aljaradi, Mansour A.; Alzahrani, Adel A. (International Journal of Health Sciences, 2020)
Melanoma is a rare tumor in Saudi population. Therefore, diagnosing melanoma among Saudi population in unexpected location is difficult without high-index of suspicion and the help of laboratory investigation methods including ancillary immunohistochemical studies. Here, we present the first reported case of anorectal melanoma in the central region of Saudi Arabia and the second reported case in the whole country. This is a report of 59-year-old Saudi female patient showed abdominal large rectal mass. Urgent colonoscopy examination revealed large fungating rectal mass with ulcerated surface. The microscopic examination of these biopsies showed colonic mucosa with a lamina propria infiltrated by pleomorphic atypical round/oval neoplastic cells arranged in sheets, clusters, and trabecular patterns. The immunohistochemical stains showed neoplastic cells are positive for S100 and Melan-A with negative for CKpan, CK7, CK20, CDX2, CD45, DOG1, chromogranin, & synaptophysin. Overall diagnosis revealed that this was a case of primary anorectal melanoma.